Tooth autotransplantation gives teeth a second chance at life: A case series. Issue 4 (April 2023) - Ji, Hao; Ren, Lizhi; Han, Jiali; Wang, Qianqian; Xu, Caixia; Fan, Yufeng; Zhang, Wei; Ge, Xuejun; Meng, Xiaorui; Yu, Feiyan
Abstract: Traditional transplantation, surgical extrusion and intentional replantation procedures are important treatment options that clinicians may consider performing in their daily clinical practice. There should be a well-constructed treatment plan for teeth with problems. In this paper, we present a series of case reports on three treatment methods used in autologous tooth transplantation and a literature review on the prevention of postoperative complications and the advantages of autologous tooth transplantation compared to dental implantation. The purpose of this study was to improve the understanding of autologous tooth transplantation.